2021
DOI: 10.1111/ijcs.12673
|View full text |Cite
|
Sign up to set email alerts
|

Women’s financial well‐being: A systematic literature review and directions for future research

Abstract: The study of financial well‐being has gained attention in recent years and a number of scholarly articles have pointed to gender‐related differences and their antecedents and consequents. The continuous growth of scholarly literature on women’s financial well‐being and its dispersion impose difficulties for researchers to comprehensively assess the state of knowledge on the topic. In this context, the objectives of this research are to conduct a systematic literature review of women’s financial well‐being and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 128 publications
1
48
0
2
Order By: Relevance
“…The findings of this study are consistent with many previous studies, for instance, we found a positive association between financial literacy, financial self-efficacy, and financial empowerment. Scholars like Lusardi and Mitchell (2007a,b, 2008, Tufano (2010, 2009), Postmus (2010Postmus ( , 2011a, Kim and Chatterjee (2013); Ali et al (2015), Karakurum-Ozdemir et al (2019), andGoncalves et al (2021) believe that financial literacy is an important determinant of financial well-being and financial empowerment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of this study are consistent with many previous studies, for instance, we found a positive association between financial literacy, financial self-efficacy, and financial empowerment. Scholars like Lusardi and Mitchell (2007a,b, 2008, Tufano (2010, 2009), Postmus (2010Postmus ( , 2011a, Kim and Chatterjee (2013); Ali et al (2015), Karakurum-Ozdemir et al (2019), andGoncalves et al (2021) believe that financial literacy is an important determinant of financial well-being and financial empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Philippas and Avdoulas (2020) and Goncalves et al (2021) highlight the gendered gap in financial literacy and financial well-being in the literature. Although there is some research available on financial literacy among women in developed countries, there exists sparse evidence on financial literacy and financial empowerment in developing countries and particularly in traditionally male-dominated and religious societies like Saudi Arabia, where men are the breadwinners and are responsible for handling finances and the related decisionmaking.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations